ANALISIS KESULITAN MAHASISWA MENYELESAIKAN SKRIPSI - Asmawan Asmawan (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2016)
This research discussed the difficulties of students in completing the skripsi (thesis). The research problems were the factors that cause the length of students in completing the thesis, as well as solutions to overcome the problems of old students in completing the thesis. The respondents were accounting education students of the Faculty of Teaching and Education who took courses thesis and proved by the study plan (KRS). The research used purposive sampling technique. This was a qualitative research. Data collection techniques were documentation, interviews and observation. The triangulation technique used to validate the data. The research found several factors that hinder the completion of the thesis. The first factor was the inability of students in writing; the external factor was the difficulty in communicating with the supervisor. While supporting factors were the motivation, a supportive environment and management system.